Adaptación a la población mexicana del Cuestionario de Orientación al Ego y a la Tarea en el Deporte (TEOSQ) - López Walle, Jeanette M.; Balaguer Solá, Isabel; Tristán Rodríguez, José Leandro; Castillo Fernández, Isabel María; Lluís Meliá, Josep (2011)
The objective of the study was to analyse the psychometric properties (factor structure and reliability) of the TEOSQ (Task and Ego Orientation in Sport Questionnaire; Duda, 1989) when adapted to the Mexican context and to ascertain whether there were any gender-contingent differences. The questionnaire was distributed to 239 athletes from 14 different kinds of sport competing in the 2008 National Children’s and Youth Olympiad with an age range of 12 to 18 years (M = 14.56, SD = 1.67). The confirmatory factor analysis supported the structure of the instrument obtained in previous studies (Task Orientation and Ego Orientation). The instrument also showed an acceptable internal consistency (a = .85 and a = .85 respectively). Gender differences indicated that girls showed greater task orientation than boys.